The epistemic, ethical, and political dimensions of uncertainty in integrated assessment modeling. (24th June 2016) - Beck, Marisa; Krueger, Tobias
Abstract : Integrated assessment models (IAMs) of global climate change that combine representations of the economic and the climate system have become important tools to support policymakers in their responses to climate change. Yet, IAMs are built in the face of pervasive uncertainty, both scientific and ethical, which requires modelers to make numerous choices in model development. These modeling choices have epistemic, ethical, and political dimensions. First, modeling choices determine how well our current (lack of) knowledge about the elements and processes of the modeled system is represented. Second, modeling choices have ethical implications, for example, the choice of a social discount rate, which is well documented. For other modeling choices, the ethical assumptions and implications are more subtle. Third, climate‐economic models are not produced and used in a political vacuum; they shape and are shaped by the social relations they are embedded in. We review findings from various literatures to unpack the complex intersection of science, ethics, and politics that IAMs are developed and used in. This leads us to suggest theoretical frameworks that may enable an integrated epistemic–ethical–political understanding of IAMs and increase transparency about all three dimensions of model uncertainties. WIREs Clim Change 2016, 7:627–645. doi: 10.1002/wcc.415 This article is categorized under: Integrated Assessment of Climate Change > Integrated Assessment Modeling